Tren Fesyen Hijab Tiktok yang Memotivasi Cara Berpakaian Islami - Yayuh Khufibasyaris (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. The existence of the hijab fashion trends on TikTok has penetrated in the campus environment. TikTok is one of the social media most often used by The Students Class of 2019, Faculty of Dakwah Unisba. The phenomenon of the hijab fashion trends on TikTok affects the interest in dressing in the Islamic way follows the trend among the TikTok users. Based on this, researchers conducted the study entitled “The Hijab Fashion Trend that Motivated The Islamic Way of Wearing Clothes.” This research aims to know the hijab fashion trend on TikTok is already in accordance with Syari’at Islam or not and to find out motivation of The Student Class of 2019, Faculty of Dakwah, Bandung Islamic University follows the hijab fashion trend on TikTok. This research uses qualitative method with 7 people informants. Data obtained from interviews, observations, library studies, and documentation. The results obtained from this study: (1) there are hijab fashion trends exist that appropriate Islamic rules and also there are hijab fashion trends not appropriate Islamic rules, (2) there are the factors of student motivation following the hijab fashion trend on TikTok, intrinsic factors and extrinsic factors. Abstrak. Eksistensi tren fesyen hijab TikTok telah merambah di lingkungan kampus. TikTok merupakan salah satu media sosial yang paling sering digunakan oleh Mahasiswi Fakultas Dakwah Unisba Angkatan Tahun 2019. Fenomena tren fesyen hijab di TikTok memengaruhi minat berpakaian Islami mengikuti tren di kalangan pengguna TikTok. Berdasarkan hal tersebut, peneliti melakukan penelitian dengan judul “Tren Fesyen Hijab Tiktok Yang Memotivasi Cara Berpakaian Islami”. Penelitian ini bertujuan untuk mengetahui tren fesyen hijab di TikTok sudah sesuai dengan syari’at Islam atau tidak dan mengetahui motivasi Mahasiswi Unisba Fakultas Dakwah Angkatan Tahun 2019 mengikuti tren fesyen hijab di TikTok dalam berpakaian Islami. Penelitian ini menggunakan metode kualitatif dengan informan yang berjumlah 7 orang. Data diperoleh melalui wawancara, observasi, studi pustaka, dan dokumentasi. Hasil yang didapatkan dari penelitian ini: (1) tren fesyen hijab di TikTok ada yang sudah sesuai dengan syari’at Islam dan tidak, (2) faktor-faktor motivasi mahasiswi mengikuti tren fesyen hijab yaitu faktor intrinsik dan faktor ekstrinsik.